Elevated histone H3 acetylation is associated with genes involved in T lymphocyte activation and glutamate decarboxylase antibody production in patients with type 1 diabetes. Issue 1 (26th June 2018) - Wang, Yanfei; Hou, Can; Wisler, Jonathan; Singh, Kanhaiya; Wu, Chao; Xie, Zhiguo; Lu, Qianjin; Zhou, Zhiguang
Abstract: Aims/Introduction: Genetic and epigenetic mechanisms have been implicated in the pathogenesis of type 1 diabetes, and histone acetylation is an epigenetic modification pattern that activates gene transcription. However, the genome‐wide histone H3 acetylation in new‐onset type 1 diabetes patients has not been well described. Accordingly, we aimed to unveil the genome‐wide promoter acetylation profile in CD4 + T lymphocytes from type 1 diabetes patients, especially for those who are glutamate decarboxylase antibody‐positive. Materials and Methods: A total of 12 patients with new‐onset type 1 diabetes who were glutamate decarboxylase antibody‐positive were enrolled, and 12 healthy individuals were recruited as controls. The global histone H3 acetylation level of CD4 + T lymphocytes from peripheral blood was detected by western blot, with chromatin immunoprecipitation linked to microarrays to characterize the promoter acetylation profile. Furthermore, we validated the results of particular genes from chromatin immunoprecipitation linked to microarrays by using chromatin immunoprecipitation quantitative polymerase chain reaction, and analyzed the transcription level by real‐time quantitative polymerase chain reaction. Results: Elevated global histone H3 acetylation level was observed in type 1 diabetes patients, with 607 differentially acetylated genes identified between type 1 diabetes patients and controls by chromatin immunoprecipitation linked to microarrays. The hyperacetylated genes were enriched in biological processes involved in immune cell activation and inflammatory response. Gene‐specific assessments showed that increased transcription of inducible T‐cell costimulator was in concordance with the elevated acetylation in its gene promoter, along with positive correlation with glutamate decarboxylase antibody titer in type 1 diabetes patients. Conclusions: The present study generates a genome‐wide histone acetylation profile specific to CD4 + T lymphocytes in type 1 diabetes patients who are glutamic acid decarboxylase antibody‐positive, which is instrumental in improving our understanding of the epigenetic involvement in autoimmune diabetes. Abstract : Patients with type 1 diabetes displays a distinct histone H3 acetylation profile in gene promoters in CD4+ T lymphocytes. Elevated histone H3 acetylation is associated with genes involving in T lymphocyte activation. GAD antibody production in T1D patients was associated with the hyperacetylation and increased expression of co‐stimulator ICOS.